Evaluation of the curing of the primer on shear bond strength of orthodontic brackets: An original research - Ekta Gupta; Tejas A Chaugule; Chaitanya Gurrala; Gaurab Jyoty Nath; C V Padma Priya; Vishal S Kudagi (Wolters Kluwer Medknow Publications, 2024)
Background: The aim of this study was to evaluate the effect of separately curing the unfilled resin for increased bond strength of the orthodontic brackets as the literature shows both studies that support and contradict this aspect. Methodology: The sample consisted of 120 specimens randomly grouped into four of 30. The tooth was cleaned of tissue and debris and stored in a distilled water solution until the procedures of bonding. The surface of the enamel was conditioned with pumice, and acrylic blocks were designed for the tooth to be mounted onto them. The buccal surfaces of all the teeth were prepared by etching the enamel with 37% phosphoric acid for a time period of 30 seconds and washed for 20 seconds under running water. Stainless steel brackets (Victory Series™ MBT, 0.022 Slot) were used for all the samples in the study, and the bonding procedure was conducted on the same day for all the groups. The artificial saliva was used for the storage of samples for 24 h after bonding, and shear bond strength testing was conducted using an Instron machine in shear or peel mode at a crosshead speed. Results: The highest mean bond strength calculated was for the conventional technique (17.45 mpa), while it was the lowest for no primer adhesive (11.21 mpa). Group IV had a greater distribution of ARI scores than groups I, II, and III. Conclusion: Group IV achieved the highest bond strength when compared to other groups, with an ARI score of 3. Group III had less bond strength, likely due to incomplete curing of the primer due to insufficient exposure to light. Transbond XT can be used without primer, making bonding, debonding, and cleaning procedures easy and less time-consuming.